Constitutional Transformation and Public Power: Reinterpreting the Separation of Powers in Contemporary Indonesia - Marzuki; Abdul Rahman (Polit Journal Scientific Journal of Politics, 2026)
The transformation of constitutional governance in the twenty-first century has fundamentally altered the distribution and exercise of public power. The classical doctrine of the separation of powers, originally designed to prevent the concentration of authority among the legislative, executive, and judicial branches, is increasingly challenged by the emergence of independent constitutional institutions, administrative agencies, decentralized governance, and collaborative policymaking mechanisms. In Indonesia, constitutional reforms following the 1998 democratic transition have significantly reshaped institutional relationships, expanding the architecture of public authority beyond the traditional framework of trias politica. These developments raise fundamental constitutional questions regarding whether the classical doctrine of the separation of powers remains adequate for explaining the contemporary structure of state power. This study aims to reinterpret the doctrine of the separation of powers within the context of Indonesia's contemporary constitutional system by examining the transformation of public power in the modern administrative state. Employing a normative legal research approach, the study analyzes constitutional provisions, statutory regulations, Constitutional Court decisions, and comparative constitutional theories alongside contemporary scholarship on constitutional governance and administrative constitutionalism. The findings demonstrate that Indonesia has experienced a significant constitutional transformation in which public power is no longer exercised exclusively through the interaction of the three classical branches of government. Instead, constitutional authority is increasingly distributed across independent institutions, regulatory agencies, decentralized governmental entities, and collaborative governance networks that perform constitutionally significant public functions. Consequently, the traditional doctrine of the separation of powers requires reinterpretation to accommodate these institutional developments while preserving the fundamental principles of constitutionalism, democratic accountability, and the rule of law.